Zur Geologie und Morphologie des Ifengebirgsstockes (Allgäu): Erläuterungen zur topographisch-morphologischen Kartenprobe VI 3: Alpiner Karst und Bergsturz - Schmidt-Thomé, Paul (ERDKUNDE, 1960)
In the area of the Hohe Ifen the geological conditions are particularly conducive to Alpine karst for mation. The rock affected, the Helvetic Schrattenkalk (lapies limestone, lower Cretaceous: Apt), which is on an average about 100 m. thick, lies on a base of clayey-marley Drusherg-Schichteny which impedes the draining away of the karst water and gives rise to rock falls of the Schrattenkalk which, if other conditions are also suitable, slides down on this surface. The area is moderately folded; denudation on the whole has gone only as far down as the Schrattenkalk which now provides the dominant note of the landscape of this mountain massif. Morphology and structure agree with each other harmoniously. Stretches with horinzontal stratification between the individual anticlines have been particularly affected by karst formation because Schrattenkalk there gives rise to plateaux. The prominent karst features found are Karrenfelder (lapies fields) and Karrengassen (lapies lanes), and they follow regularly shaped systems of cracks and fissures. Dolines occur only at lower altitudes beneath the upper limit of forest. Since the karst features are no more than a few metres in size, they cannot be shown by the 20 m. contour lines. However, as the sample map VI 3 shows, the karst features could be represented surprisingly clearly by using additional rock line drawing and the kantographic method.